Behoeftebepaling in die leksikografie - Alberts, Mariëtta (Lexikos, 1992)
Needs Assessment in Lexicography The value of dictionaries lies in their contribution towards eliminating obstacles in communication. It is of great importance to undertake studies to assess the needs of dictionary users in order to compile effective dictionaries. There are enough indications in the relevant literature to show that needs assessment should take place regularly and that comparative studies are necessary. A literature study shows that different kinds of needs assessment studies have been undertaken in the field of lexicography. Unfortunately there is still no model for assessing lexicographical needs. Because of the nature of the needs assessment studies and lack of proper documentation on the research, follow-up studies are not possible. Owing to gaps in existing lexicographical studies it is necessary to lean heavily on the examples of needs assessment studies in peripheral disciplines. Different variables (i.e. the characteristics of users and social factors) can have an influence on behaviour and therefore on the interpretation of the results of an empirical investigation. The influence of the variables on the dictionary user and on his job performance is discussed. The different relevant characteristics of the concepts "needs", "information needs", "information user" and "needs assessment" are dealt with at length and related to the dictionary user and the practice of lexicography. A model to assess the needs of dictionary users is suggested. This lexicographical needs assessment model is based on different needs assessment studies taken from the information sciences as well as on the systems approach model. An attempt was made to take all the relevant information into account in developing the lexicographical needs assessment model.